KAJIAN YURIDIS TERHADAP KETERLIBATAN IBU KANDUNG DALAM KASUS TINDAK PIDANA PERDAGANGAN ORANG (STUDI PUTUSAN NOMOR 1451/Pid.Sus/2021/PN Mdn) - Christanti Natalia; Diding Rahmat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Human trafficking is a serious violation of human rights that frequently The crime of human trafficking is one of the most serious violations of human rights, often involving vulnerable groups, particularly women and children. Despite the issuance of various regulations, the phenomenon of human trafficking in Indonesia remains prevalent, even within family environments. This study discusses the involvement of a biological mother in the crime of child trafficking based on Decision Number 1451/Pid.Sus/2021/PN Mdn. The research method used is normative juridical with a case approach and a statutory approach supported by secondary data. Based on the findings, the legal provisions regarding the crime of human trafficking in Indonesia are firmly regulated in Article 2 paragraph (1) of Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking, which states that any person committing the crime of human trafficking shall be punished with imprisonment for a minimum of 3 years and a maximum of 15 years, and a fine of at least IDR 120,000,000. Furthermore, Article 76F in conjunction with Article 83 of Law Number 35 of 2014 on Child Protection prohibits the economic and sexual exploitation of children, with a maximum penalty of up to 15 years in prison. These legal provisions are reinforced by Indonesia’s ratification of the Palermo Protocol through Law Number 14 of 2009, as part of its international commitment to combat human trafficking, especially against women and children. In this case, the panel of judges declared that the defendant, Hanita Sari Nasution, as the biological mother of the victim, was legally and convincingly proven to have committed the crime of human trafficking by employing her daughter as a commercial sex worker for seven years. The blood relationship was considered an aggravating factor, as the defendant had abused her authority as a parent. The panel sentenced the defendant to 4 (four) years of imprisonment and a fine of IDR 120,000,000, as stated in Decision Number 1451/Pid.Sus/2021/PN Mdn. This ruling reflects the application of the principle of equality before the law and child protection within Indonesia’s national criminal justice system